Educational practices in motion: a scoping review of embodied learning approaches in school - Faella, Pierluigi; Digennaro, Simone; Iannaccone, Alice (Frontiers in Education, 2025)
IntroductionEmbodied learning integrates physical activity, cognition, and environmental interaction within educational practices, challenging traditional dichotomies between mind and body. In the context of physical education (PE), embodied approaches are particularly promising for fostering physical literacy, embodied identity, and interdisciplinary learning, thereby promoting more inclusive and holistic pedagogical models.MethodsA scoping review was conducted in accordance with the Joanna Briggs Institute guidelines and the PRISMA checklist. A systematic search across Web of Science, Scopus, and PubMed databases was performed from January to November 2024. Studies were included if they empirically explored embodied learning within school-based PE contexts. Twenty-one studies met the inclusion criteria and were analyzed thematically. The methodological quality of the studies was assessed using the Mixed Methods Appraisal Tool (MMAT).ResultsThree major thematic cores emerged: physical literacy, embodied identity, and multidisciplinarity. Embodied learning interventions consistently enhanced student motivation, body awareness, cognitive engagement, and interdisciplinary integration, particularly in STEM-related areas. Furthermore, several studies reported improvements in students’ self-perception, social competence, and critical engagement with body ideals. Despite these positive outcomes, limitations were noted, including cultural homogeneity of samples, age-related research gaps, and methodological inconsistencies across studies.DiscussionEmbodied learning holds substantial potential to enrich educational environments by bridging physical, cognitive, and emotional domains of student experience. It facilitates deeper engagement, inclusivity, and academic integration across disciplines. However, future research should focus on diversifying cultural contexts, including broader age ranges, and conducting longitudinal studies to explore the sustained impact of embodied learning interventions.